The Specific Features of Scientific Supervision over the Production of Promising RadioElectronic Devices - Lavrich, Yu.M. (Science and Innovation, 2024)
Introduction. The development of new generations of weapons and military equipment is accompanied by the scientific supervision that is a necessary condition for achievement of high- performance characteristics, at all stages. Purpose. The purpose of this work is to substantiate possible ways and methods for scientific supervision under current conditions. Materials and Research Methods. The problems of weapons and military equipment production under current conditions have been analyzed. Research results. Based on the conducted analysis a few modifications to scientific supervision have been offered, in particular: to renew applied-research science within the existing academic structures, to establish a system for management of defensive research and development works (DRDW) based on the principals of interconnected and coordinated participation of all scientific spheres, to audit and to assess the existing scientific and technical reserves, to create their common bank, to provide access to the systematized scientific and technical information, to revise approaches to assessment of national scientometric base, to create national periodicals concerning the production of weapons and military equipment, to correct the methodology for selection and evaluation of competitive suggestions from R&D institutions. Conclusion. The offered modifications to the content of scientific supervision over the design, development, and production of new weapons and military equipment generations will enable not only to reduce the duration of stages of development and introduction of new armament models, but also to improve the quality of serial products.